Sustaining TBLT during Online Learning: The Role of EFL Teacher Agency - Dias Fatatin Birrina; Ive Emaliana (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
While task-based language teaching (TBLT) is among the most preferred methods for teaching foreign languages, it has not received enough study to be empirically verified in the English as a Foreign Language (EFL) classroom. Few studies have looked into instructors' reactions towards TBLT in the setting of Indonesian college English. This study contributes to closing the gap by studying EFL teachers' perspectives of TBLT and evaluating the present use of TBLT in online learning. Data from classroom observations, interviews, and course materials were triangulated to give a descriptive synthesis of teacher participants' experiences with TBLT instruction. The data analysis indicated that the teacher displayed proactive and reactive agencies in overcoming the conflicts in the instructional activity system via teaching as both learning and adaptation. A variety of mediational elements were revealed to account for their agency. In order to influence teachers' adoption of task-based language teaching, the study emphasizes the significance of teachers' shared attitudes regarding the usefulness of TBLT, curricular change, and institutional support. The article finishes with a discussion of the practical implications of the findings of this small-scale study on how to facilitate successful application of TBLT during emergency remote teaching in Indonesia.